2015
DOI: 10.3382/ps/peu078
|View full text |Cite
|
Sign up to set email alerts
|

Impact of commercial housing systems and nutrient and energy intake on laying hen performance and egg quality parameters

Abstract: The US egg industry is exploring alternative housing systems for laying hens. However, limited published research related to cage-free aviary systems and enriched colony cages exists related to production, egg quality, and hen nutrition. The laying hen's nutritional requirements and resulting productivity are well established with the conventional cage system, but diminutive research is available in regards to alternative housing systems. The restrictions exist with limited availability of alternative housing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
22
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 31 publications
6
22
0
2
Order By: Relevance
“…In the present study, the mortality rate was found to be similar in different cage tiers (P > 0.05) which was lower compared to other studies [24]. There are several others reporting lower mortality rates in furnished cages when compared to the conventional cage systems [27,28] and in noncage systems [29,30].…”
Section: Mortalitysupporting
confidence: 58%
“…In the present study, the mortality rate was found to be similar in different cage tiers (P > 0.05) which was lower compared to other studies [24]. There are several others reporting lower mortality rates in furnished cages when compared to the conventional cage systems [27,28] and in noncage systems [29,30].…”
Section: Mortalitysupporting
confidence: 58%
“…An extensive collaborative comparison of commercial conventional cage, enriched colony cage, and cage-free aviary hen housing systems has been conducted by a team of researchers in the US. Five sustainability areas were investigated: hen health and well-being, environmental impact, food safety and quality, food affordability, and worker health and safety (Jones et al., 2014 , 2015 ; Arteaga et al., 2015 ; Karcher et al., 2015 ; Matthews and Sumner, 2015 ; Mitchell et al., 2015 ; Regmi et al, 2015 ; Shepherd et al., 2015 ; Zhao et al., 2015a , 2015b ; Blatchford et al, 2016 ; Campbell et al, 2016a , 2016b ). The multi-year, multi-flock study has produced a large repository of information intended for egg industries, regulatory groups, and consumers to make informed decisions about commercially available hen housing systems.…”
Section: Introductionmentioning
confidence: 99%
“…Much lower (w40%) mortalities were reported in hens in conventional caging compared to an aviary system. 110 Moreover, there was a greater incidence of keel deformities in hens in a cage free system compared to those in conventional cages. 111 There are also differences in leg bone characteristics with hens under the cage free conditions having increased cortical cross-sectional area and cortical density of their humerus and tibia compared to those maintained in conventional cages.…”
Section: Approaches To Reduce Broodinessmentioning
confidence: 96%
“…114 In another study, egg production was greater in hens with an enriched environment compared to conventional caging. 110…”
Section: Approaches To Reduce Broodinessmentioning
confidence: 99%